PENGEMBANGAN E-LKPD MENGGUNAKAN NEARPOD BERBASIS RADEC UNTUK SISWA KELAS IV SEKOLAH DASAR - Sri Mutiara; Firman; Desyandri (STKIP Subang, 2024)
This study aims to develop and implement Nearpod-based E-LKPD with the RADEC (Read, Answer, Discuss, Explain, Create) learning model to improve the effectiveness of learning in elementary schools. Based on a preliminary study at SDN 05 Padang Pasir, it was found that the use of conventional LKPD was not interesting enough and effective in increasing student engagement. Therefore, the development of interactive technology-based E-LKPD is expected to support more enjoyable and effective learning. This study uses the Research and Development (R&D) method with the ADDIE model which includes five stages: analysis, design, development, implementation, and evaluation. The trial subjects were 19 fourth-grade students of SDN 05 Padang Pasir. The results showed that Nearpod-based E-LKPD had a very good level of practicality and validity, with scores of 91.67% and 90.33%, respectively. The effectiveness of the media was also proven to increase, indicated by an increase in student learning outcomes from 52.63% who achieved the KKM before implementation, to 84.21% after using this media. This study concludes that the use of Nearpod-based E-LKPD can significantly increase student engagement and learning outcomes, as well as support more interactive and enjoyable learning.